Mutasynthesis of medicinally significant natural products through manipulation of gene governing starter unit - Grover P.; Sharma D.K.; Chhalodia A.K.; Mukherjee D. (My University, 2025)
Most of the biologically active microbial natural products and their analogs bear a complex molecular architecture. The semisynthetic modifications and stereospecific diver-sity-oriented synthesis of these native natural products to generate analogs are difficult and time-consuming. Mutasynthesis is a powerful tool that utilizes the microorganism's genetic and metabolic engineering skills to produce derivatives of complex natural products of microbial origin. Mutasynthesis is based on the cellular uptake of chemically modified intermediates from the culture media and their addition to the secondary metabolism by mutant mi-croorganisms. This review will describe the importance of mutasynthesis in the generation of complex microbial secondary metabolites. We have covered a literature search on mutasyn-thesis over the last ten years (2011-2020) in this review. © 2021 Bentham Science Publishers.